Burden of HIV among young transgender women: factors associated with HIV infection and HIV treatment engagement. Issue 1 (2nd January 2019) - Jin, Harry; Restar, Arjee; Biello, Katie; Kuhns, Lisa; Reisner, Sari; Garofalo, Robert; Mimiaga, Matthew J.
ABSTRACT: Young transgender women (YTW) are disproportionately affected by HIV, however, little is known about the factors associated with HIV infection and treatment engagement. We examined correlates of HIV infection and the steps of the HIV treatment cascade, specifically, being aware of their HIV infection, linked to care, on ART, and adherent to ART. We analyzed the baseline data of Project LifeSkills, a randomized control trial of sexually active YTW recruited from Chicago, Illinois and Boston, Massachusetts. We conducted multivariable Poisson regressions to evaluate correlates of HIV infection and the steps of the HIV treatment cascade. Nearly a quarter (24.7%) of YTW were HIV-infected. Among HIV-infected YTW, 86.2% were aware of their HIV status, 72.3% were linked to care, 56.9% were on ART, and 46.2% were adherent to ART. Having avoided healthcare due to cost in the past 12 months and not having a primary care provider were associated with suboptimal engagement in HIV care. Our results suggest that improving linkage and retention in care by addressing financial barriers and improving access to primary care providers could significantly improve health outcomes of YTW as well as reduce forward transmission of HIV.